The Relationship between Weight as Well as the Kind of Prostate Hypertrophy and the Response to Tamsulosine, a Specific ?-Blocker - Mombini, Hayat (Urology Journal, 2009)
Purpose: To study the effects of Tamsulosine (Flowmax) as a specific ?-blocker in patients with prostate weighted less than 40 g and lacked median lobe and to compare them to patients with prostate weighted more than 40 g with median lobe. Materials and Methods: Forty outpatients with BPH were referred to clinic and intentionally enrolled in this study. Patients were divided into 2 groups of 20 patients. Tamsulosine was daily administered for all of them for 6 weeks. Routine tests were performed for all patients, all of which were normal. The probability of prostate cancer was ruled out. The size of prostate and type of hypertrophy were determined by one radiologist via DRE, suprapubic ultrasonography and TRUS-P. Patients were divided into A and B groups according to the size of prostate and the lack of median lobe or its presence. Prostate size was less than 40 mg in group A and all patients lacked median lobe; whereas, prostate size was more than 40 mg (between 40-60 mg) in group B and patients had some median lobe. Results: An increase of 30% in base line Q Max and a decrease of 25% in base line IPSS was seen in 16 patients (80%) of group A, while these were observed only 9 patients (45%) of group B. Conclusion: Determination of prostate size and the type of hypertrophy seems to be essential before any Tamsulosine administration. The weight of prostate is determined by protoscan.